Removal of As(V) compounds from water using OPMN-P nanofiltration membrane - Melnyk, Lyudmyla O. (My University, 2016)
High efficiency of removal of As(V) compounds from water with nanofiltration technique was shown. OPMN-P nanofiltration membrane was involved to investigations, which were performed within a wide range of pH,concentration of background electrolyte, operating pressure and permeate recovery (25-90%). The rejection has been found to reach 93-98%. As shown, the membrane is promising for water purification from arsenic, the maximal contaminant level is 10 μg/dm3. As(III) has to be oxidized preliminarily down to As (V) using photocatalysis.
Keywords: arsenate; drinking water; nanofiltration; membrane; арсенати; питна вода; нанофільтрація; мембрана